A selecção dos pesticidas na luta contra os inimigos da macieira - Amaro, Pedro (2009)
To perform pesticide risk communication, namely concerning new toxicological, ecotoxicological and environmental knowledge, consequence of the Directive 91/414/CEE, it is indispensable to secure the convenient divulgation, in the Pesticide Guides of DGPC and of Pesticide Companies, overtaking their actual SILENCE, almost generalized about these problems. With this paper we seek to give that information concerning the authorized pesticides, in Portugal, in apple crop, in order to allow pesticide selection.